PENINGKATAN KESIAPSIAGAAN MASYARAKAT MENGHADAPI BENCANA DENGAN KOMUNIKASI YANG EFEKTIF (DESA KADEMANGAN) - Sarinah Sihombing; Elferida Sormin; Titiek Surya Ningsih; Ummy Hanifa; Mikhael Farreli Simarmata (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2025)
ITL Trisakti with several private universities under the coordination of LLDikti III, including Universitas Kristen Indonesia and Universitas Tama Jagakarsa were carried out a community outreach program in Kademangan Village, Cianjur City, aimed at increasing public awareness of disaster risks in the region. The program sought to enhance the community's ability to respond to and evacuate during disasters, emphasize the importance of effective communication in disaster preparedness, and strengthen mitigation efforts. Utilizing the Smart Village Program under the Smart People pillar, the initiative included public education, donation distribution, and the integration of Artificial Intelligence into creative teaching and learning resources for educators from five elementary schools in Kademangan Village. Post-program evaluations indicated that the activities were highly impactful, providing practical self-rescue strategies, increasing knowledge and awareness, and enabling participants to adopt preventive measures before, during, and after natural disasters to safeguard themselves and assist their families and communities.